A multilocus sequence analysis scheme for characterization of Flavobacterium columnare isolates - Ashrafi, Roghaieh (BMC Microbiol, 2015)
BACKGROUND: Columnaris disease caused by Flavobacterium columnare is a serious problem in aquaculture, annually causing large economic losses around the world. Despite considerable research, the molecular epidemiology of F. columnare remains poorly understood. METHODS: We investigated the population structure and spatiotemporal changes in the genetic diversity of F. columnare population in Finland by using a multilocus sequence typing (MLST) and analysis (MLSA) based on DNA sequence variation within six housekeeping genes. A total of 83 strains of F. columnare were collected from eight different areas located across the country between 2003 and 2012. RESULTS: Partial sequencing of six housekeeping genes (trpB, tuf, atpA, rpoD, gyrB and dnaK) revealed eight sequence types and a moderate level of genetic diversity (H = 0.460). Phylogenetic analysis of the concatenated protein-encoding gene sequence data (ca. 3,509 nucleotides) formed two lineages, which could be further divided into five clusters. All analysed F. columnare strains appeared to have a genetic origin distinct from that of another important fish pathogen form the genus Flavobacterium, F. psychrophilum. Although the value of the index of association between alleles, 0.292 (P < 0.001), supports some degree of clonality for this species in Finland, recombination has introduced molecular diversity to the population almost three times more than mutation. CONCLUSION: The results suggest that Finnish F. columnare strains have an epidemic population structure followed by clonal expansion of successful genotypes. Our study with reproducible methodology and comparable results establishes a robust framework for the discrimination and phylogenetic analysis of F. columnare isolates, which will help to improve our understanding about geographic distribution and epidemiology of columnaris disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12866-015-0576-4) contains supplementary material, which is available to authorized users.